[Si4]4– and [Si9]4– Clusters Crystallized from Liquid Ammonia Solution – Synthesis and Characterization of K8[Si4][Si9]·(NH3)14.6. Issue 2 (2nd December 2016) - Benda, Christian B.; Henneberger, Thomas; Klein, Wilhelm; Fässler, Thomas F.
Abstract : The extraction of the silicide K12 Si17 with liquid ammonia in the presence of a sequestering agent and AuPPh3 Cl or Zn(Cp*)2 led to crystals of the solvate compound K8 [Si4 ][Si9 ]· (NH3 )14.6, which was characterized by single‐crystal X‐ray diffraction. It is the first compound with an isolated and ligand‐free [Si4 ] 4– cluster obtained from solution. It also contains one [Si9 ] 4– cluster per formula unit, whereas the precursor K12 Si17 is built from [Si4 ] 4– and [Si9 ] 4– clusters with a 2:1 ratio. Abstract :